Evaluación de los parámetros de validación en el método para la determinación de cobre, plomo, zinc, fierro y plata por espectrofotometría de absorción atómica de flama en muestras de cabeza del laboratorio químico MAHR túnel de volcán compañía minera S.A.A. U.E.A. yauli - Alayo Rodríguez, Jorge Luis (2009)
The present work sought to guarantee the results obtained in the chemical laboratory Mahr Túnel de Volcan Compañía Minera S.A.A. U.E.A. Yauli by evaluating the validation parameters in a test method of said laboratory. The accuracy of the method was determined by the veracity and precision analysis by the method of standard addition with sample, the selectivity by the method of "type I analysis: power, dissolution and uniformity of content - comparison of the behavior of samples enriched with analyte with respect to the standard behavior enriched with analyte ", the limit of detection by comparison of white and white enriched to a single concentration and the limit of quantification as 3 times the limit of detection, the linearity was determined by validating the calibration curve of the Perkin Elmer AAnalys 100 atomic absorption equipment; the sensitivity was the slope of the calibration curve, the robustness of the method was determined by means of the Youden and Steiner procedure taking as variables the addition of 5 to 10 mL of hydrochloric acid, addition of 5 to 10 mL of nitric acid and temperature of attack between 200 and 300 ºC; Finally, the uncertainty of the method was evaluated by calculating the expanded uncertainty. After the experimental development it was demonstrated that the studied method is accurate, selective, linear, robust; and the sensitivity of the Perkin Elmer AAnalys 100 atomic absorption equipment, the instrumental detection and quantification limits and the uncertainty as expanded uncertainty were determined